Intervensi Psikologis Berbasis Komunitas melalui Pelatihan Teamwork untuk Meningkatkan Efektivitas Tim pada Komunitas Kader RW II di Wilayah Kelurahan X di Surabaya - Kartika Cahyaningtyas; Diah Sofiah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
ABSTRACT The purpose of this study was to examine teamwork problems among community volunteers (Kader Hebat Surabaya—KSH) of RW II in Kelurahan X, Surabaya, and to implement a psychoeducational intervention to improve team effectiveness and communication quality. This community-based psychological service aimed to identify interpersonal barriers affecting collaboration and to enhance members’ social cohesion, trust, and coordination skills through experiential teamwork training at the community level. Materials and Methods. The study employed a mixed qualitative and quantitative approach involving observation, interviews, and psychological testing using the Teamwork Quality Questionnaire (TWQ). Seventeen active KSH members aged 27–56 years participated in the intervention. Data were analyzed descriptively and through paired sample t-tests to assess pre- and post-intervention changes. Results. Findings revealed that most participants demonstrated low teamwork quality characterized by poor communication, unclear coordination, and minimal emotional support among members. Specifically, 82% of cadres were reluctant to express opinions, 79% felt task division was unclear, and 70% lacked peer support. The teamwork training—which included psychoeducation on communication, coordination, empathy, and collaborative games such as “Tebak 1 Kata” and “Perkakas Lapangan”—led to significant improvement in teamwork understanding and interaction. Statistical analysis showed a notable increase in post-test scores (M = 60.00) compared to pre-test scores (M = 42.35; t = -8.752, p = 0.000), confirming the intervention’s effectiveness. Conclusions. The teamwork psychoeducation program effectively enhanced communication, coordination, and group solidarity among community health volunteers. Sustained mentoring by coordinators, ongoing reflection forums, and continuous community-based psychological support are recommended to maintain behavioral change and promote long-term team cohesion. Keywords: Community teamwork, psychoeducation, communication skills, cadre training, community-based intervention